The use of Life Cycle Assessment and the Leopold Matrix to analyze environmental aspects and impacts in a handmade soap production industry - Willon José Trindade Filho; Thyago de Melo Duarte Borges; Bruna Carvalho da Silva; Valquíria Melo Souza Correia (Gestão & Produção)
Abstract Since the earliest concepts of production methods, natural resources have been fundamental to the growth of the manufacturing sector. However, certain industries, such as cleaning product manufacturing, generate harmful environmental impacts, leading to resource scarcity. This study aimed to use the Leopold Matrix and Life Cycle Assessment (LCA) to identify and classify the environmental aspects and impacts in an artisanal soap production business in a town in Rio Grande do Norte, Brazil. Through a case study, environmental aspects were mapped, prioritizing actions to mitigate the most critical impacts, such as solid waste generation, gas emissions, natural resource consumption, and effluent discharge. The Leopold Matrix and LCA highlighted environmental impacts that contribute to ozone layer degradation, soil and groundwater contamination, air pollution, and effects on wildlife. Based on these findings, the study proposes obtaining ISO 14.001 certification, using renewable energy, controlling emissions, implementing a waste management plan, and establishing partnerships with recycling companies. This study is relevant for micro and small businesses in the cleaning and cosmetics sectors, their suppliers, regulatory agencies, and sustainability-focused organizations, offering a replicable and adaptable methodology for microenterprises. The scientific community also benefits from the combined application of LCA and the Leopold Matrix, expanding the discussion on environmental responsibility. Future research may explore the effectiveness of these proposals and extend the methodology to other sectors with similar production characteristics.